ANALISIS KETERSEDIAAN FASILITAS UMUM TERHADAP KEPUASAN PENGHUNI KOMPLEK PERUMAHAN BEUTARI PERMAI DESA BAYU KECAMATAN DARUL IMARAH KAB. ACEH BESAR - Fika Arfiana Tanjung; Mochammad Afifuddin; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The Bayu Village is one of the villages located in Darul Imarah Sub-district, Aceh Besar District, the Aceh Province. The abundance of vacant land in Bayu Village, prompting the desire of investors to be converted into the development of a housing residential. Based on the observation, public facilities in Beutari Permai residential are still inadequate, such as mosque, Green Open Space (GOS), and garbage station. Limited public facilities provided by developers could lead to lack of satisfaction from home buyers (users). This study aims to analyze the relationship and influence between the availability of public facilities to the satisfaction of residents of Beutari Permai residential. Further, analyzing the effect of the availability of public facilities on the satisfaction of the residents of Beutari Permai residential is performed. This research uses qualitative method through observation and interview, and quantitative method through questionnaires survey data. Target respondents in this study are residents of housing consist of 51 respondents. Statistical methods used in data processing are validity and reliability test. While data analysis consists of descriptive statistics, simple correlation, and multiple linear regression. The statistical analyses performed by using Statistical Product and Service Solution (SPSS)  software. The results show that drainage and road facilities have a very high relationship, drinking water facilities have a sufficient relationship, sanitation facilities have a low relationship, while the electricity network facilities have a very low relationship to the satisfaction of the residents of Beutari Permai residential. The availability of public facilities consisting of roads, sanitation, drainage, drinking water and electricity networks have a positive effect on the satisfaction of residents of the Beutari Permai residential. The availability of public facilities consisting of road facilities, sanitation, drainage, drinking water, and electricity network simultaneously has contributed 82.4% to the satisfaction of residents of the Beutari Permai residential.